Magnetohydrodynamics flow of micropolar Cu-TiO2 hybrid nanofluid with heat generation - Rahimah, Jusoh; Zulkhibri, Ismail; Mohd Hisyam, Ariff; Roslinda Nazar, Nazar; Ioan Pop, Pop; Nadirah, Mohd Nasir; Nooraini, Zainuddin (AIP Publishing, 2025)
As an alternative heat transfer fluid, hybrid nanofluid has demonstrated tremendous promise; therefore, ongoing research must focus on enhancing its thermal conductivity. This paper seeks to address the impacts of heat generation and magnetic field on a micropolar hybrid nanofluid that comprises nanoparticles of titanium dioxide and copper. The numerical solutions for the mathematical equations governing the micropolar hybrid nanofluid model are attained through the application of appropriate similarity transformations and the bvp4c codes generated by Matlab software. The findings suggest that elevated heat generation results in a concomitant rise in the temperature of the micropolar hybrid nanofluid. Graphic representations of the effects of micropolar parameter, suction and magnetic parameter are also provided. Furthermore, a stability analysis is conducted, revealing that while the first solution generated exhibits stability, the second solution does not.